(untitled) (Journal Of Educational and Psychological Researches, 2012)
Occupies an important geographical position, and instructional material is distinctive among the various course materials, as covered in the study of human and surrounding environment, and interaction happening between them, and the problems that arose as a result and a lot of reliable in achieving educational purposes. Through the monotony and tradition in the methods used in our schools in the teaching of geography, which prevails in teaching nature conservation and indoctrination with poor educational qualification as a teacher geography, and the fact that this article need to be effective methods for teaching, such as the use of teaching models modern-dependent student at the center of the process education, and this is confirmed by modern education. From here, the researcher considered a modern style workout in the teaching of geography is the use of a specimen and you and Carey is one of the most widely used models in instructional design process and highlights the basic instructional design used in many training positions in the sectors of business, industry, government and military. The present study aimed to know the effect you have a specimen in the collection and Carrie first intermediate students in the subject of geography. The use of experimental design with control partial as deliberately seeking to choose a school and one in middle school at the Directorate General for Education Baghdad Rusafa third, and more deliberate and chosen randomly Division (a) to represent the ABG control and who has studied the traditional way, and the Division of (b ) to represent the first experimental group which studied the use of a specimen Dick & Carey. The number of students in both groups (58) by a student (29) students in the control group and (29) student in the group, and was rewarded with students between the two groups in a variable pre-testing, and chronological age, and monthly income, and parental level of achievement and intelligence. Researcher has prepared plans for teaching specific subjects for the experiment and then prepared a test for the acquisition of concepts for each topic. By (30) test paragraph, paragraphs and analyzed statistically was the difficulty level of the vertebrae of the test ranged between (0.75-0.77), while the power of discrimination ranged between paragraphs (0.30-0.77). Researcher and confirmed the veracity of the test by submitting it to a group of experts, and by persistence statistically using Pearson’s correlation coefficient, as the stability coefficient (0.77), and the experiment lasted for two months for research. And results of the experiment resulted in the superiority of the experimental group the control group students.